2013
DOI: 10.1161/circimaging.113.000253
|View full text |Cite
|
Sign up to set email alerts
|

Massive Left Atrial Thrombus in a Patient With Rheumatic Mitral Stenosis and Atrial Fibrillation While Anticoagulated With Dabigatran

Abstract: The online-only Data Supplement is available at http://circimaging.ahajournals.org/lookup/suppl

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…Although Dabi appears to be an effective alternative to warfarin in preventing stroke or systemic embolism without requiring PT–INR monitoring, the fact that 4% of patients receiving Dabi still had LA thrombus in our survey suggests that TEE is useful when performed before elective ECV of persistent AF. Thrombus may develop even under Dabi treatment in the presence of mechanical heart valves or rheumatic mitral stenosis [12,13], but a few cases of failure to prevent LA thrombus formation with the use of this agent have also been reported in patients with AF without such backgrounds [14–16]. Although it is hard to prove, we speculate that not only higher CHADS 2 scores, but also the insufficient Dabi dosage given to some of our patients might have led to inadequate anticoagulation and subsequent clot formation.…”
Section: Discussionmentioning
confidence: 77%
“…Although Dabi appears to be an effective alternative to warfarin in preventing stroke or systemic embolism without requiring PT–INR monitoring, the fact that 4% of patients receiving Dabi still had LA thrombus in our survey suggests that TEE is useful when performed before elective ECV of persistent AF. Thrombus may develop even under Dabi treatment in the presence of mechanical heart valves or rheumatic mitral stenosis [12,13], but a few cases of failure to prevent LA thrombus formation with the use of this agent have also been reported in patients with AF without such backgrounds [14–16]. Although it is hard to prove, we speculate that not only higher CHADS 2 scores, but also the insufficient Dabi dosage given to some of our patients might have led to inadequate anticoagulation and subsequent clot formation.…”
Section: Discussionmentioning
confidence: 77%
“…Despite the theoretical differences in the pathophysiological characteristics of thrombosis between patients with and without valvular AF, cases of left atrial thrombosis in severe rheumatic mitral stenosis, despite treatment with dabigatran, have been reported. 30 In our study, we did not exclude patients with rheumatic valvular disease, and we believe it may be unsafe to extrapolate our findings to the group of patients with hemodynamically significant rheumatic valvular disease, who represent a minority of our patient population.…”
Section: Discussionmentioning
confidence: 97%
“…It has also been used in patients with atrial fibrillation who had documented left atrial thrombus, proving its role in resolution of thrombus [ 4 , 5 ]. However, left atrial thrombus formation on dabigatran therapy as in our case has been reported in 3 other cases in the literature till date [ 6 , 7 ]. Sharma et al [ 6 ] recently reported two cases of left atrial thrombus formation on dabigatran therapy for chronic atrial fibrillation.…”
Section: Discussionmentioning
confidence: 70%